La brecha entre formación y empleo en el perfil profesional radiofónico: estudio de caso de las emisoras generalistas y universitarias de Castilla y León - Dr Miguel Ángel DÍAZ MONSALVO, (Fonseca, Journal of Communication, 2023)
The constant changes brought about by the radio as a mass media have caused a redefinition in the professional profile, which concerns the educational system as well as initiatives such as college radios. Through a study case based on surveys and a focus group, the main general radio station directors from Castile and León and graduates with different careers and profiles analyze the skills that define the radio profile, both those that are demanded and those that are developed.